2019
DOI: 10.3389/fpsyg.2019.00094
|View full text |Cite
|
Sign up to set email alerts
|

Emotion in Context: How Sender Predictability and Identity Affect Processing of Words as Imminent Personality Feedback

Abstract: Recent findings suggest that communicative context affects the timing and magnitude of emotion effects in word processing. In particular, social attributions seem to be one important source of plasticity for the processing of affectively charged language. Here, we investigate the timing and magnitude of ERP responses toward positive, neutral, and negative trait adjectives during the anticipation of putative socio-evaluative feedback from different senders (human and computer) varying in predictability. In the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 74 publications
(163 reference statements)
0
11
0
Order By: Relevance
“…By contrast, emotion effects at very early temporal stages are more sporadically observed (cf., Citron, 2012 ). Studies that detected such early effects, report amplified amplitudes on P1, peaking between 80 and 120 ms (e.g., Hofmann et al, 2009 ; Scott et al, 2009 ; Bayer et al, 2012 ; Schindler et al, 2019b ), and/or on N1 between 100 and 200 ms post stimulus. They are typically valence-specific and often more pronounced for negative words (e.g., Scott et al, 2009 ; Kissler and Herbert, 2013 ; Yao et al, 2016 ; Schindler et al, 2019b ), but have also been reported selectively for positive, e.g., happiness-related words ( Briesemeister et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…By contrast, emotion effects at very early temporal stages are more sporadically observed (cf., Citron, 2012 ). Studies that detected such early effects, report amplified amplitudes on P1, peaking between 80 and 120 ms (e.g., Hofmann et al, 2009 ; Scott et al, 2009 ; Bayer et al, 2012 ; Schindler et al, 2019b ), and/or on N1 between 100 and 200 ms post stimulus. They are typically valence-specific and often more pronounced for negative words (e.g., Scott et al, 2009 ; Kissler and Herbert, 2013 ; Yao et al, 2016 ; Schindler et al, 2019b ), but have also been reported selectively for positive, e.g., happiness-related words ( Briesemeister et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“… Scott et al (2009) further showed an interaction of emotion with word frequency on the N1 in that the N1 was larger for high- than low-frequency negative words, whereas neutral words showed the opposite frequency modulation. Addressing neural effects of attributed social contexts, Schindler et al (2019b) recently observed that valence effects on early brain potentials such as the N1 were elicited only when emotional trait adjectives were embedded in personally relevant communicative context—as a feedback personally targeted at the participant. When devoid of social embedding, the same emotional words elicited only late ERP amplifications (LPP).…”
Section: Introductionmentioning
confidence: 99%
“…The amplitude of the P300 (P3) component has also been studied in performance monitoring research. Slightly larger P3 peaks were sometimes attributed to more positive feedback but were generally not statistically significant (Potts, 2011; Yi et al, 2018; Schindler et al, 2019; Tunison et al, 2019). One study compared a consumer-grade MUSE EEG system and the clinical-grade Brain Vision ActiChamp system and found that the FRN responses were similar in a selection task (Krigolson et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Both components are sensitive to verbal affective person-related information associated with faces via verbal evaluative learning (for instance, EPN: Abdel Rahman, 2011 ; Kissler and Strehlow, 2017 ; Wieser et al , 2014 ; Suess et al , 2015 ; Junghöfer et al , 2016 ; Luo et al , 2016 ; Xu et al , 2016 ; LPP: Luo et al , 2016 ; Baum et al , 2018 ). Crucially, the LPP is sensitive to additional information such as context and relevance, putting emotional contents into perspective ( Schacht and Sommer, 2009b ; Herbert et al , 2011 , 2013 ; Blechert et al , 2012 ; Rellecke et al , 2012 ; Schindler et al , 2019 ), whereas the EPN is relatively independent of task demands and the relevance of emotional contents in a given context ( Schacht and Sommer, 2009b ; Herbert et al , 2011 , 2013 ). It is noteworthy that this evidence of additional contextual influences on ERPs comes from studies testing the effects of emotional information immediately, while there is scarce evidence of such contextual effects on later consequences ( Baum et al , 2018 ).…”
mentioning
confidence: 99%